2022
DOI: 10.1111/1460-6984.12786
|View full text |Cite
|
Sign up to set email alerts
|

People with aphasia and their family members proposing joint future activities in everyday conversations: A conversation analytic study

Abstract: Background: In everyday conversations, a person with aphasia (PWA) compensates for their language impairment by relying on multimodal and material resources, as well as on their conversation partners. However, some social actions people perform in authentic interaction, proposing a joint future activity, for example, ordinarily rely on a speaker producing a multi-word utterance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…By the late 1990s/early 2000s, this resulted in an increasing interest generally in more naturally occurring conversations than constructed assessment scenarios, but utilized more theoretical sociolinguistic frameworks for analysis, e.g., Conversation Analysis Ferguson, 1996;Simmons-Mackie & Damico, 2009) and Systemic Functional Linguistic approaches (Armstrong & Mortensen, 2006). This approach has continued to develop to the present day (Beeke & Bloch, 2023;Groenewold & Armstrong, 2018;Hersh et al, 2018Hersh et al, , 2024Tuomenoksa et al, 2023;Wilkinson, 2015). While the examination of the language of a particular speaker in a monologic context tells us a lot about the speaker's language "system" and access to certain types of word and sentence processing, it is during everyday interactions that the speaker's true sociolinguistic strengths and weaknesses become apparent.…”
Section: Incorporating a More Interactional Focus To Discourse Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By the late 1990s/early 2000s, this resulted in an increasing interest generally in more naturally occurring conversations than constructed assessment scenarios, but utilized more theoretical sociolinguistic frameworks for analysis, e.g., Conversation Analysis Ferguson, 1996;Simmons-Mackie & Damico, 2009) and Systemic Functional Linguistic approaches (Armstrong & Mortensen, 2006). This approach has continued to develop to the present day (Beeke & Bloch, 2023;Groenewold & Armstrong, 2018;Hersh et al, 2018Hersh et al, , 2024Tuomenoksa et al, 2023;Wilkinson, 2015). While the examination of the language of a particular speaker in a monologic context tells us a lot about the speaker's language "system" and access to certain types of word and sentence processing, it is during everyday interactions that the speaker's true sociolinguistic strengths and weaknesses become apparent.…”
Section: Incorporating a More Interactional Focus To Discourse Analysismentioning
confidence: 99%
“…Of course, much has to do with the conversational partners they encounter and the way(s) in which the partners react to and allow for any aphasic difficulties of the person with aphasia, as well as their relationships with those partners. While many early examinations of the conversational skills of people with aphasia focused primarily on the person with aphasia, more recent studies have been able to capture both speakers' contributions to conversational interactions (Beeke & Bloch, 2023;Tuomenoksa et al, 2023;Wilkinson, 2015), with a limited number of studies, as noted earlier, capturing multiparty conversations such as those found in aphasia groups.…”
Section: Incorporating a More Interactional Focus To Discourse Analysismentioning
confidence: 99%